Application of the stationary echo cancellation technique (SEC) in ultrasonic doppler measurements of blood flow in children's hearts - FILIPCZYŃSKI, L.; NOWICKI, A.; CHROŚCICKI, A. (Archives of Acoustics, 1982)
The authors used an ultrasonic Doppler system based on the technique of the cancellation of stationary echoes (SEC) with an built-in conventional single-gate Doppler pulse flowmeter for recording blood flow rates in large vessels and cavities in children's hearts. The SEC technique facilitates considerably noninvasive investigation and identification of blood flow, as it permits the visualization of the blood velocity distribution over the whole depth of structures penetrated by an ultrasonic beam. The present system also permits records of blood velocities at chosen depths to be obtained. Examples of the visualization and records of blood velocities in large vessels and cavities of the heart are given.